2000
DOI: 10.1038/sj.bjp.0703665
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase is a site of superoxide synthesis in endothelial cells treated with glyceryl trinitrate

Abstract: Tolerance to glyceryl trinitrate (GTN) involves superoxide (O2.−) production by endothelial cells. Nitric oxide synthase (NOS) produces O2.− when L‐arginine (L‐arg) is limited. The purpose of this study was to test the hypothesis that GTN stimulates NOS to increase O2.− synthesis in endothelial cells when L‐arg is limited. Production of O2.− by bovine aortic endothelial cells (BAEC, passages 3–5) was determined by spectrophotometrically measuring superoxide dismutase‐inhibited reduction of ferricytochrome C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 27 publications
2
28
1
3
Order By: Relevance
“…These results indicate that GTN has marked oxidant effects on endothelial cells. These results are in concert with our previous studies (Abou-Mohamed et al, 2000;Kaesemeyer et al, 2000). This endothelial dysfunction and tolerance to GTN may be mediated, at least in part, by ROS such as superoxide and peroxynitrite, tyrosine nitration, and the ␣-and ⑀PKC isozymes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results indicate that GTN has marked oxidant effects on endothelial cells. These results are in concert with our previous studies (Abou-Mohamed et al, 2000;Kaesemeyer et al, 2000). This endothelial dysfunction and tolerance to GTN may be mediated, at least in part, by ROS such as superoxide and peroxynitrite, tyrosine nitration, and the ␣-and ⑀PKC isozymes.…”
Section: Discussionsupporting
confidence: 79%
“…formation (Dikalov et al, 1998;Kaesemeyer et al, 2000). Both vitamin C and the normal substrate for NOS, L-arginine, reduce O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ing conclusion of this study is that H 2 O 2 is generated by the action of the eNOS. The proposal that eNOS can generate oxygen-derived free radicals is not unprecedented (13)(14)(15), but the notion that this happens physiologically, in normal mouse arteries exposed to acetylcholine, is novel. These conditions differ dramatically from those in which NO synthase has been observed to produce oxygen-derived free radicals, namely the absence of normal substrates or cofactors (13,14).…”
Section: H 2 O 2 and Vascular Relaxationmentioning
confidence: 99%
“…7 Although membrane-bound oxidases have been considered responsible for the increased superoxide anion production, 3 recent experimental data suggested that abnormalities in nitric oxide synthase (NOS) function might also contribute. 6,8 The mechanism for the NOS-dependent superoxide production remains uncertain, and a number of hypotheses have been proposed, 6,8,9 including reduced availability of tetrahydrobiopterin, a cofactor for NOS, and/or L-arginine, its substrate. 6,8 Supplemental tetrahydrobiopterin has been shown to reverse NOS dysfunction in conditions of increased oxidative stress, such as hypercholesterolemia, chronic smoking and, recently, GTN treatment.…”
Section: See P 1086mentioning
confidence: 99%